Factors that contribute to the sustainability of 5s implementation in management agencies at Jabatan Ketua Menteri Melaka, Seri Negeri / Siti Noorain Suratman - Suratman, Siti Noorain (2012)
This study aims to identify the factors that contribute to the sustainability of 5S implementation in Management agencies at Jabatan Ketua Menteri Melaka. The factors are reward, leadership, internal audit and commitment. Questionnaires were used to obtain the finding of this study where concerned of 108 respondents. The questionnaire distributed divided into three sections. Section A: Demographic, Section B: Factors that contribute to sustainability of 5S and Section C: The impact of Sustainability of 5S. The data was analyzed using the Statistical Package for Social Sciences (SPSS) Window Release 20.0. The researcher used Pearson Correlation and Multiple Regression Analysis to examine and test the hypotheses of this study and to answer the research questions. Result of the Pearson Correlation Analysis showed that there was significant relationship between all independent variables; Reward factor, Leadership factor, Internal Audit factor and Commitment factor towards the sustaining of 5S implementation in organization. Thus, the Multiple Regression showed that the Leadership factor is the most significant and most dominant factor that contributes to the sustainability of 5S in organization. The implication of this study can help the organization to identify and analyze the factor that needs to be focus beside to improve and being the successful competitor in the marketplace.